PSXI-36 Effects of antifungal and fibrinolytic inoculants on fermentation quality, rumen digestibility, and aerobic stability of rye silage harvested at early dough stage - Paradhipta, Dimas Hand Vidya (J Anim Sci, 2019)
This study estimated the effects of new inoculants on fermentation quality and rumen digestibility of rye silage with different moisture contents. New inoculants were isolated for producing antifungal substances (Lactobacillus brevis 100D8) and fibrinolytic enzymes (Leuconostoc holzapfelii 5H4), and mixed at 1:1 ratio. Rye forage was harvested at 20 days after heading stage, and chopped into 3–5 cm length. The chopped forage ensiled immediately (high moisture, High) or after 8 h wilting (low moisture, Low) into 10-L mini silo (8kg) with new inoculants at 7.5 × 105 cfu/g (MIX) or commercial inoculant (L. plantarum CMbio) at 8.0 × 105 cfu/g (LPT) for 100 days in quadruplicate. Wilting process did not affect chemical compositions of rye forages, except dry matter (DM) content (P < 0.001; 42.8 vs. 34.7%) was higher in High than in Low. Rye silage in High had lower (P < 0.001) DM with higher (P < 0.05) neutral detergent fiber (NDF), and in vitro digestibilities of DM (IVDMD) and NDF (IVNDFD) than in Low. Additionally, NDF (P < 0.01), hemicellulose (P = 0.005), IVDMD (P = 0.005), and IVNDFD (P = 0.045) of rye silages were higher in MIX than those in LPT. Rye silage had lower (P < 0.05) pH by High or MIX application. Acetate concentration of rye silage was higher (P < 0.01) in MIX than in LPT, but lower (P < 0.001) lactate to acetate ratio. Yeast was lower (P = 0.006) in MIX than in LTP. There were the interaction effects (P < 0.05) between moisture and inoculant on ammonia-N, lactate, propionate, lactic acid bacteria, and aerobic stability of rye silage. Therefore, this study could conclude that new inoculant improved the fermentation quality of rye silage harvested at early dough stage, which showed the beneficial effects on rumen digestibility with high moisture rye forage and on aerobic stability with low moisture. [Image: see text] [Image: see text] [Image: see text] [Image: see text]